Algorithmic Human Resources Management – Perspectives and Challenges - Łukasz Sienkiewicz (Annales Universitatis Mariae Curie-Skłodowska Sectio H, Oeconomia, 2021)
Theoretical background: Technology – most notably processes of digitalisation, the use of artificial in telligence, machine learning, big data and prevalence of remote work due to pandemic – changes the way organizations manage human resources. One of the increasing trends is the use of so-called “algorithmic management”. It is notably different than previous e-HRM or HRIS (human resources information systems) applications, as it automates HR-related duties. Algorithms, being autonomous computational formulae, are considered objective and mathematically correct decision-making mechanisms. Limiting human in volvement and oversight of the labour process might lead to serious ethical and managerial challenges. Many areas – previously being sole responsibility of managers (including HR managers), like employment relations, hiring, performance management, remuneration – are increasingly affected, or even taken over, by algorithmic management.